Siltation increases the susceptibility of surface‐cultured eastern oysters (Crassostrea virginica) to parasitism by the mudworm Polydora websteri. (11th February 2017) - Clements, Jeff C; Bourque, Daniel; McLaughlin, Janelle; Stephenson, Mary; Comeau, Luc A
Abstract: Mudworm ( Polydora websteri ) parasitism is known to result in unsightly mud blisters in eastern oysters ( Crassostrea virginica ), resulting in reduced product quality and increased vulnerability to illness and environmental stress. While typically a concern only for bottom‐grown oysters, an abnormal severe outbreak of P. websteri in surface‐cultured oysters in New Brunswick, Canada, was reported in 2013, along with an anecdotally reported concurrent increase in siltation. Although heavier loads of silt are reported to increase P. websteri infestations in oysters, studies report mixed effects of siltation to this regard. Here, we report the results of a field experiment testing the effect of siltation on P. websteri recruitment in surface‐grown oysters at an aquaculture site in Richibucto, New Brunswick. Live oysters of similar size were deployed at the aquaculture site and were left to collect P. websteri recruits under one of two siltation treatments (high vs. low) for 50 days. Results suggested that P. websteri recruitment correlated with metrics of oyster size (shell weight, length, width, depth and surface area). When P. websteri counts were standardized for oyster shell morphometry, P. websteri recruitment was significantly higher in oysters exposed to the high siltation treatment, accumulating approximately 1.5× as many P. websteri as oysters exposed to the low siltation treatment. Our results suggest that higher amounts of siltation on surface‐cultured oysters can result in increased rates of P. websteri parasitism. Enhanced cleaning regimes may help to alleviate the impacts of P. websteri in surface‐grown oysters, although other mitigation strategies exist.